A Study of the Formation of Velocity Counter Lines and Secondary (Spiral) Flows in Different Cross Sections of Divergent, Convergent and Uniform Arcs - Liaghat, A.; Tavanpour, N. (Engineering, Technology & Applied Science Research, 2017)
The mechanical properties of flow are very complex in channel arcs. Therefore, dynamic numerical models of fluids are considered effective tools in predicting such flow fields. In this study, the numerical model was validated by the measures of a uniform U-shaped arc with a width of 0.6 meter. Then two similar U shaped arcs, divergent and convergent, were simulated by a three-dimensional numerical model with variable widths from 0.6 to 0.75 meters and 0.6 to 0.45 meters. Validating the numerical model by measured data in the uniform 180-degree arc showed that the model can simulate the flow field in the uniform arc very well. Results regarding several parameters such as rout of maximum velocity, maximum velocity line, water level variations, power of spiral flow, existence of a rotating cell are stated and discussed.